Non-Career Teachers in the Design Studio: Economics, Pedagogy and Teacher Development. - Smith, Korydon; Smith, Carl (International Journal of Art & Design Education, 2012)
As the economic pressure to teach more students with fewer (and less costly) instructors has increased in higher education, the utilisation of non-career teachers has become more prevalent. Design education has not escaped this phenomenon; non-career teachers, such as graduate and undergraduate students or design practitioners, have become commonplace in design education, including the design studio. The studio, however, is a unique teaching and learning environment in higher education. It poses distinct socio-academic challenges for both students and teachers. The utilisation of non-career teachers in studios raises a number of ethical and pedagogical questions. Teacher development is one serious concern. Here, the authors articulate the major challenges confronted by non-career studio teachers, especially student teaching assistants, and strategies for their development.